292 Emergency airway management outside the operating room; a three year prospective service evaluation and quality improvement project. Issue 12 (23rd November 2020) - Horner, Daniel; Daniels, Benjamin; Murray, Nicola; Allen, Gareth; Baylis, Claire
Abstract : Aims/Objectives/Background: Emergency airway management outside a controlled theatre environment has been previously associated with a high rate of adverse events. Several initiatives to improve safety (such as video laryngoscopy, checklists, simulation training etc..) have been studied in isolation. It remains unclear as to whether these interventions have been embedded in the Emergency Department (ED) and whether they offer cumulative marginal gains in safety. Methods/Design: A prospective 3-year service evaluation delivered at a major trauma and neurosciences centre between 2016 and 2019. We designed a rolling quality improvement program to mitigate procedural airway risk through collaborative multidisciplinary team (MDT) working, education and transparent metrics. PDSA cycles included documentary guidance (including flowcharts and checklists), high fidelity simulation training, equipment redesign, prefilled medications and mandatory reporting items (figure 1 ). Results/Conclusions: We analysed prospectively collected data on 1181 intubation episodes outside a theatre environment over a 39 month period, of which 575 (48.7%) were performed out of hours and 635 (53.8%) were performed in the ED. Bedside consultant presence and periprocedural checklist use both showed a sustained increase during the study period. Use of ketamine and thiopentone as primary induction agents increased and decreased, respectively (figure 2). Cricoid pressure and video laryngoscopy (VL) utilisation rates remained relatively static throughout, as did a first pass success (FPS) rate of between 83.0 to 93.5%. Composite major complications (including sustained hypotension and/or critical hypoxia) were significantly reduced during the study period, as demonstrated via statistical process chart (SPC) mapping (figure 3). In conclusion, we found a quality improvement program to be associated with a sustained reduction in the risk of major complications following emergency airway management. This improvement was not explained by simple direct changes in procedural care, such as the use of VL or technique changes resulting in improved FPS, but may have been influenced by unknown confounding variables.